Communicative conflict in the genre of Internet comment (on the material of commentsof the social network «VKontakte») - Piskun, Ekaterina V. (Journal of the Belarusian State University. Philology, 2024)
The genre of Internet comment is considered, which has a high potential for the development of conflicts caused by the specifics of Internet communication. The types and features of Internet comments, components and phases of communicative conflicts are analysed. Various types of conflictogens are being studied. The research shows that the majority of Internet comments are conflicting. The development of a conflict is characterised by the use of various tactics of verbal confrontation, and its completion is characterised by the use of tactics to neutralise the conflict.
Keywords: Internet communication; Internet comment; communicative conflict; conflictogen